PEMBUATAN E-CATALOGUE SEBAGAI MEDIA PROMOSI DI INSTAGRAM MENGGUNAKAN APLIKASI CANVA PADA UMKM YY KEBAB KERTOSONO - Hafidz Musthofa Fakhriadi; Dwi Sudjanarti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
E-Catalogue is a promotional medium that facilitates the process of finding and managing information about the products and services of a company or organization. So far, media promotions have been carried out only to close friends of the seller and local residents. The problem that arises is the lack of promotion through online media. The purpose of this research was to create promotional media in the form of an e-catalog of products using Canva which displays a good design and can be understood by consumers in order to attract the attention and taste of buyers to the products of micro small and medium enterprise Kebab YY, Kertosono Branch. The method used in this study was the action research method (planning, acting, observing, reflection). The data collection methods used were interviews, questionnaires, observation, and documentation. Product catalogs that have been made are evaluated by distributing questionnaires to 20 respondents consisting of the owner, 2 design experts, 2 marketing experts, and 15 consumers. Measuring the level of design effectiveness used the EPIC model (emphaty, persuasion, impact, communication). The results of the analysis showed that in cycle 1 the design still could not be published because in the first cycle they received suggestions and some gave ineffective judgments from owners, computer experts, marketing experts and consumers so they had to be corrected again. The result value of the EPIC score in cycle II is at 4.1 so that it can be interpreted as effective and worthy of publication. Based on the results of the research that has been done, it can be concluded that the e-catalogue for UMKM Kebab YY products at the Kertosono Branch can be used as a marketing medium, so that it can provide convenience in conveying product information to customers